Oxidative DNA Damage and NOX4 Levels in Children with Undescended Testes - Avci, Veli; Ayengin, Kemal; Alp, Hamit Hakan (European Journal of Pediatric Surgery, 2019)
Background Undescended testis (UDT) is a common urological disorder. Patients with UDT have a risk of malignancy and infertility. The development of these conditions may be due to oxidative stress mediated by reactive oxygen species. The aim of this study was to investigate the relationship between these parameters by detecting oxidative DNA damage (8-hydroxy 2 deoxyguanosine/106 deoxyguanosine), ischemia-modified albumin (IMA), malondialdehyde (MDA), and nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) levels in children with UDT and healthy control group.Materials and Methods The blood samples were obtained from 30 patients with UDT and 40 healthy male subjects. The levels of oxidative DNA damage were detected by high-pressure liquid chromatography method. We used commercially available kits that use enzyme-linked immunosorbent assay method to measure IMA, MDA, and NOX4 levels.Results The levels of MDA, IMA, NOX4, and oxidative DNA damage in children with UDT were statistically significantly higher than control group. In addition, we found that the levels of NOX4, IMA, and oxidative DNA damage after 12 months of age was significantly higher than before 12 months of age.Conclusion We identified increased lipid peroxidation, oxidative DNA damage, IMA, and NOX4 levels in children with UDT. Delay in the treatment of UDT may cause oxidative damage. That is why, according to us the antioxidant treatment may be beneficial in children with UDT.
Keywords: undescended testis; ischemia-modified albumin; malondialdehyde; NOX4; oxidative DNA damage